Physico-chemical properties of salt-fermented commercial fish sauces in Thailand - Byoung Mok Kim (2018)
In this study, the characteristic components of commercially available fish sauces from Thailand were investigated. Moisture, ash, crude protein and crude fat content was 51.8-59.5 %, 20.8-28.3 %, 11.4-20.6 % and 0.1-0.6 %, respectively. Salinity was 19.1-28.0 % and the volatile base nitrogen content was the highest in TF10 (298.8 mg %) and the lowest in TF3 (19.1 mg %). pH was in the range of 5.1-5.8. The total nitrogen content was 1.8-3.5 g % and was the highest in TF5. Amino nitrogen content was 406.0-1,750.0 mg % and was the highest in TF6. Lightness, redness and yellowness were 34.7-53.3, 10.68-28.79 and 4.74-36.06, respectively. Major organic acids were acetic acid, lactic acid, propionic acid and butyric acid and the total amount of organic acid was 1.11-7.06 mg/L. The total amount of free amino acids was 1,103.7-9,581.8 mg % and the major free amino acids were aspartic acid, glutamic acid, glycine, alanine, methionine, isoleucine and phenylalanine. Umami amino acid was the highest in TF11, while sweet amino acid (SA) and bitter amino acid (BA) were the highest in TF1 and TF11, respectively. The ratio of SA/BA was the highest in TF8; essential and non-essential amino acid were the highest in TF11 and TF1, respectively. The aroma pattern measured using an electronic nose differed depending on each product.